Panasonic: MX-801SHG Blender / Mohammad Syafirul Nazreen Ridzuan - Ridzuan, Mohammad Syafirul Nazreen (2021)
Panasonic is a well-known company that manufacturer of electrical and electronic products in Kadoma, Osaka. This company has been chosen to be analyse in this case study under the subject of Technology Entrepreneurship (ENT600) code. This case study is to figure out about the background of company, organizational structure, products and services of Panasonic Company. One of the product have been chosen from the Panasonic Company is MX-801SHG Blender. Thus, the business, marketing and operating strategies used by the Panasonic Company has been figure out to see how the company manage the production of their product into the target market. Next, there are some problems that I figure out about this MX-801SHG Blender by using SWOT analysis. All the information about the MX-801SHG Blender has been studied. Due to the needs and demands by the existing users of the MX-801SHG Blender, there have several problem that face by Panasonic Company. They have an issues with the control settings for the blender, the design and material that use to make the blade and also the design and material that use to make blender container. After discovering the product issues, I also find the solution based on the limitations that the company should design. This will help the business find ways of overcoming and satisfying the needs of their customers by making their product to be more unique. The company should address the problems with all the solution suggested in order to develop the new product to target the market in the future. At last, in order to enhance the goods and services, some suggestions can be made. They can improve the material of the blender container by using glass material to make it more resistant toward variety of food and temperature. Other than that, the company should provide more speed choices which have three speed ranges from low to high that can be used for all kinds of food and can also make the control settings to be in automatic. All the recommendations are very useful to the Panasonic Company and can serve as a catalyst for improving their product research and innovation. As a consequence, the Panasonic Company will manufacture a lot of electrical and electronics goods that are more high tech. Not only that, it will support customers as well as enable the company to boost their profits.